Peculiarities of Trust and Distrust in Students of Higher Schools of Economics - L A Jouravleva; V A Sumarokova (Peoples' Friendship University of Russia (RUDN University), 2014)
The present study introduces the results of the empiric research of different types of trust. It also reveals some peculiarities of the manifestation of trust and distrust towards people in students at various stages of their professional growth.